Fusion of the COL4A5 Gene With NR2F2-AS1 in a Hemangioma Carrying a t(X;15)(q22;q26) Chromosomal Translocation - PANAGOPOULOS, IOANNIS (Cancer Genomics Proteomics, 2020)
Background/Aim: Hemangiomas are benign neoplastic proliferations of blood vessels. Cytogenetic information on hemangiomas is limited to four tumors with abnormal karyotypes. We report here a solitary chromosomal translocation and its molecular consequence in a hemangioma. Materials and Methods: A cavernous hemangioma was extirpated from the foot of a 62 years old man and genetically studied with cytogenetic and molecular genetic methodologies. Results: G-Banding analysis of short-term cultured tumor cells yielded the karyotype 46,Y,t(X;15)(q22;q26)[4]/46,XY[12]. RNA sequencing detected fusion of the collagen type IV alpha 5 chain gene (COL4A5 on Xq22.3) with intronic sequences of nuclear receptor subfamily 2 group F member 2 antisense RNA 1 (NR2F2-AS1 on 15q26.2) resulting in a putative COL4A5 truncated protein. The fusion was verified by RT-PCR together with Sanger sequencing and FISH analyses. Conclusion: The involvement of COL4A5 indicates that some hemangiomas have pathogenetic similarities with other benign tumors such as leiomyomas and subungual exostosis.